Lack of access and continuity of adult health care: a national population-based survey - Dilélio, Alitéia Santiago; Tomasi, Elaine; Thumé, Elaine; Silveira, Denise Silva da; Siqueira, Fernando Carlos Vinholes; Piccini, Roberto Xavier; Silva, Suele Manjourany; Nunes, Bruno Pereira; Facchini, Luiz Augusto (Revista de Saúde Pública, 2015)
OBJECTIVE To describe the lack of access and continuity of health care in adults. METHODS A cross-sectional population-based study was performed on a sample of 12,402 adults aged 20 to 59 years in urban areas of 100 municipalities of 23 states in the five Brazilian geopolitical regions. Barriers to the access and continuity of health care and were investigated based on receiving, needing and seeking health care (hospitalization and accident/emergency care in the last 12 months; care provided by a doctor, by other health professional or home care in the last three months). Based on the results obtained by the description of the sample, a projection is provided for adults living in Brazilian urban areas. RESULTS The highest prevalence of lack of access to health services and to provision of care by health professionals was for hospitalization (3.0%), whilst the lowest prevalence was for care provided by a doctor (1.1%). The lack of access to care provided by other health professionals was 2.0%; to accident and emergency services, 2.1%; and to home care, 2.9%. As for prevalences, the greatest absolute lack of access occurred in emergency care (more than 360,000 adults). The main reasons were structural and organizational problems, such as unavailability of hospital beds, of health professionals, of appointments for the type of care needed and charges made for care. CONCLUSIONS The universal right to health care in Brazil has not yet been achieved. These projections can help health care management in scaling the efforts needed to overcome this problem, such as expanding the infrastructure of health services and the workforce.